2019
DOI: 10.1002/jmri.26811
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Surveillance MR Enterography (MRE) in Asymptomatic Children and Adolescents With Crohn's Disease

Abstract: Background MR enterography (MRE) is the primary modality for evaluating small bowel disease in pediatric Crohn's patients. Standard clinical practice includes imaging patients at diagnosis and during symptomatic recurrence. The role for MRE in surveillance of asymptomatic Crohn's patients has not yet been established. Purpose To determine whether MRE imaging features are associated with clinical recurrence. Study Type Retrospective. Populations Pediatric Crohn's patients who underwent MRE while asymptomatic, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…Although barium examinations remain a formidable tool in the depiction of mucosal abnormalities, particularly the apthoid lesions of early Crohn disease [2], magnetic Life 2023, 13, 1691 2 of 15 resonance enterography (MRE) possesses the same significant advantages, namely, the delineation of extraintestinal and transmural inflammation, multiplanar evaluation, and high intrinsic soft-tissue resolution, without radiation exposure [3]. In particular, young Crohn's patients, who require appropriate diagnostic and surveillance imaging at diagnosis and during symptomatic and asymptomatic recurrence, profit from this marginally invasive method [4].…”
Section: History Overview Of Small Bowel Imagingmentioning
confidence: 99%
“…Although barium examinations remain a formidable tool in the depiction of mucosal abnormalities, particularly the apthoid lesions of early Crohn disease [2], magnetic Life 2023, 13, 1691 2 of 15 resonance enterography (MRE) possesses the same significant advantages, namely, the delineation of extraintestinal and transmural inflammation, multiplanar evaluation, and high intrinsic soft-tissue resolution, without radiation exposure [3]. In particular, young Crohn's patients, who require appropriate diagnostic and surveillance imaging at diagnosis and during symptomatic and asymptomatic recurrence, profit from this marginally invasive method [4].…”
Section: History Overview Of Small Bowel Imagingmentioning
confidence: 99%
“…• Спустя 6-12 месяцев после операции пациентам с БК рекомендовано проведение контрольного эндоскопического обследования, а при необходимости МРТ и/или КТ с контрастированием кишечника [200,205,206,207].…”
Section: уровень убедительности рекомендации -с (уровень достоверност...unclassified
“…• Оперированным пациентам с БК, при невозможности визуализировать зону анастомоза рекомендовано констатировать наличие или отсутствие рецидива, основываясь на сочетании данных рентгенологического обследования (КТ и/или МРТ с контрастированием кишечника) и неинвазивных маркеров воспаления -СРБ, ФК и др. [200,206,207,208]. • Периодичность и объем диспансерного наблюдения определяется индивидуально, но у большинства пациентов рекомендовано выполнять исследование уровня С-реактивного белка в сыворотке крови, а также исследование уровня кальпротектина в кале каждые 3 месяца [74].…”
Section: уровень убедительности рекомендации -C (уровень достоверност...unclassified
“…Another potential indication for MRE is surveillance of asymptomatic patients with Crohn disease to assess subclinical disease activity. A study of 34 children and adolescents with asymptomatic Crohn disease patients undergoing MRE surveillance [52] found that several MRE imaging features (mural edema, hyperenhancement, engorged vasa recta, and restricted diffusion) were significant predictors of disease recurrence within 6 months, with sensitivity values of 71% to 86% and specificity values of 68% to 86%. Mural diffusion restriction was found to be the best predictor by multivariate regression and predicted future disease recurrence with an AUC of 0.786.…”
Section: Variant 3: Child Known Crohn Disease Disease Surveillance Or...mentioning
confidence: 99%